Dynamic And Static Power Reduction In Wireless Sensor Node - المغرقوني يارا; خولة حموي (Latakia University Journal -Engineering Sciences Series, 2023)
Wireless Sensor Networks pervades virtually every aspect of our lives, Despite the many advantages of WSN, they are described as resource constrained networks, as the sensor nodes are batteries-powered and subject to a set of constraints imposed by memory, limited processing capacity and available bandwidth, this imposed a set of challenges on WSN’s design. Energy efficiency is one of the critical issues to extend lifetime of the nodes. In this paper, we propose a model to manage power consumption in wireless sensor node based on integration of DPM (Dynamic Power Management) technology with PG (Power Gating) technology for static power management. We relied on energy consumption and lifetime of the sensor node as the main parameters to evaluate the performance. Our model reduces up to 84.09% of power consumed, and increases the lifetime more than 6 times in the reference model.